INOVASI DALAM MANAJEMEN PENDIDIKAN SEBAGAI ELEMEN KRUSIAL DALAM MENINGKATKAN MUTU DAN EFEKTIVITAS DALAM PENDIDIKAN - Rezky Rianti; Arismunandar (STKIP Subang, 2025)
Education plays a strategic role in developing high-quality and competitive human resources. However, the challenges of globalization and technological advancements require educational institutions to reform through innovation in educational management. This study aims to analyze the role of educational management innovation in improving the quality and effectiveness of education, identify challenges in its implementation, and formulate relevant strategies to address changing times. This study employed a library research method, reviewing various literature and previous research findings related to educational innovation and management. The results indicate that educational management innovation plays a significant role in improving the quality of the learning process, the professionalism of educators, and the effectiveness of the education system. Through the application of technology, integrated quality management strategies, and collaborative leadership, educational institutions can create adaptive, creative, and student-centered learning environments. Key challenges in implementing innovation include limited resources, low digital literacy, and resistance to change. Therefore, innovative strategies are needed that focus on strengthening educator competencies, cross-stakeholder collaboration, and government policy support. In conclusion, innovation in educational management is the primary foundation for realizing a high-quality, effective, and sustainable education system in the digital era.